Evidence-Based Parenting Interventions to Promote Secure Attachment - Barry Wright MD, FRCPsych; Elizabeth Edginton PhD (SAGE Publishing, 2016)
Various interventions are used in clinical practice to address insecure or disorganized attachment patterns and attachment disorders. The most common of these are parenting interventions, but not all have a robust empirical evidence base. We undertook a systematic review of randomized trials comparing a parenting intervention with a control, where these used a validated attachment instrument, in order to evaluate the clinical and cost-effectiveness of interventions aiming to improve attachment in children with severe attachment problems (mean age <13 years). This article aims to inform clinicians about the parenting interventions included in our systematic review that were clinically effective in promoting secure attachment. For completeness, we also briefly discuss other interventions without randomized controlled trial evidence, identified in Patient Public Involvement workshops and expert groups at the point our review was completed as being used or recommended. We outline the key implications of our findings for clinical practice and future research.